Pengaruh Dosis dan Frekuensi Aplikasi Biofungisida Trichoderma terhadap Infeksi Rigidoporus microporus pada Benih Karet - Widi Amaria; Rita Harni; Edi Wardiana (Pusat Penelitian dan Pengembangan Perkebunan, 2018)
Biological agents Trichoderma virens and T. amazonicum have been developed and examined for their effectiveness through in vitro and in vivo approaches against Rigidoporus microporus, the cause of white root disease (WRD) in rubber. The effectiveness of these bio-agents can be determined by testing the dosage and frequency of Trichoderma spp. biofungicide application. The research aimed to investigate the effective dose and application frequency of Trichoderma spp. biofungicide on R. microporus infection in rubber seedling. The experiment was conducted in laboratory and screen house of Indonesian Industrial and Beverage Crops Research Institute (IIBCRI), Sukabumi, from June to December 2014. A randomized block design was used with 14 treatments and 3 replications, i.e biofungicide combination (T. virens and T. amazonicum), dosage (25, 50, and 75 g), application frequencies (1 and 2 times application), and two controls (positive and negative). Rubber seedlings used were propellegitiem seeds of GT1 clone planted in polybags. Trichoderma spp. was multiplied using fermentation method in liquid medium, whereas biofungicide was formulated using talc as carrier. Observed variables including Trichoderma spp. population number, incubation period, attack intensity, and WRD attack suppression. The results showed that T. virens and T. amazonicum biofungicides with 50 g/plant dose at one application was the most effective and efficient in suppressing R. microporus development on rubber seedlings. The type, dosage, and frequencies of application increased Trichoderma spp. population in soil, prolonged the pathogen’s incubation period, decreased WRD attack intensity, and suppress the attack of WRD disease.